Whipple’s Disease Affecting Ileal Peyer’s Patches: The First Case Report - Sabah Sid’Amar; Giacomo Puppa (Case Reports in Pathology)
Whipple’s disease is a rare chronic systemic bacterial infectious disease which can affect multiple organs, with a wide clinical spectrum encompassing many symptoms presenting in various forms and combinations. In the cases where the gastrointestinal tract is implicated, the more frequent localizations involve the small bowel, especially the duodenum. A case of a 67-year-old man who underwent clinical investigation after presenting with a progressive weight loss and showing a hypercapting right paracoeliac adenopathy at PET-CT scan is reported herein. A gastroscopy and a colonoscopy were done. The biopsies of the endoscopically normal ileal mucosa encompassed some submucosal Peyer’s patches. Histological examination of this lymphoid tissue revealed several foamy macrophages which turned out positive on periodic acid-Schiff special staining. Polymerase chain reaction of the microdissected lymph follicles allowed for confirming Whipple’s disease diagnosis. A targeted antibiotic treatment administrated to the patient led to a rapid clinical improvement. This finding of a previously unreported localization of infected macrophages in Whipple’s disease suggests that sampling the organized mucosal-submucosal lymphoid tissue may increase the diagnostic yield in endoscopic biopsies.